Preparation method of metal-doped sodium titanate negative electrode material
By directly doping metal ions with hydrolysis in sodium titanate doping technology, the process flow is simplified and the cost is reduced, and the problems of high cost and difficult to produce on a large scale in the existing technology are solved, and the quality of sodium titanate anode material is improved and electrochemical properties.
Patent Information
- Application Number
- CN202411427038.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing sodium titanate negative electrode material doping technology has problems such as high cost, low repeatability, low yield, difficulty in large-scale production, and complex process flow.
Hydrolysis using a sulfate solution of metal ions and a titanium sulfate solution was obtained to obtain a homogeneously doped metatitanic acid, which was then calcined directly with a sodium source to synthesize metal-doped sodium titanate.
The process flow is simplified, production costs and energy consumption are reduced, the quality and electrochemical properties of materials are improved, and repeated experiments and scale-up is facilitated.
Smart Images

Figure CN119390111A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a metal-doped sodium titanate negative electrode material. Background Art
[0002] With the increasing global demand for renewable energy, energy storage technology has become the key to achieving energy transformation and ensuring energy security. Among the many energy storage technologies, sodium-ion batteries are gradually becoming a strong competitor to lithium-ion batteries due to their advantages such as abundant resources, low cost and potential high energy density, especially in the field of large-scale energy storage. In sodium-ion batteries, the selection of negative electrode materials has a crucial impact on their performance, and sodium titanate, as one of the negative electrode materials, has received extensive attention and research in recent years. However, it still faces some challenges in practical applications. On the one hand, the cost is high, and the cost problem is mainly due to the synthesis method and titanium source. On the other hand, the material itself has poor conductivity, which limits its performance under high current charging and discharging. At present, more methods such as nanoengineering, morphology control, metal and non-metal coating are used, accompanied by the disadvantages of high cost, low yield and difficulty in industrial production. In fact, introducing heteroatoms into sodium titanate is an effective solution to improve conductivity, but the doping method mostly uses hydrothermal method, solid phase method, sol-gel method and other synthesis methods. The cost is high and it is difficult to produce on a large scale.
[0003] Qiu Xiaoming et al. provide a method for preparing a nickel-doped sodium titanate / graphene composite material, first preparing a precursor solution of the composite material, then preparing a sodium titanate / graphene composite material and performing nickel doping, and finally obtaining a nickel-doped sodium titanate / graphene composite material after annealing. The nickel-doped sodium titanate / graphene composite material provided by this invention has a high sodium storage capacity and good reversibility. The sodium-based dual-ion battery prepared using the above composite material has a reversible capacity of 255.4mAh / g when the current density is 0.05A / g, and has good cycle stability (CN202410100248.9). Liu Jinping et al. disclose an iron-doped sodium titanate nanoarray electrode material and a preparation method thereof, wherein the electrode material is composed of a titanium sheet as a substrate and an iron-doped sodium titanate array film, wherein the array film is assembled from interlaced sodium titanate nanosheets, the thickness of the sodium titanate nanosheets is 30 nanometers, and they are evenly and densely distributed on the surface of the titanium sheet, and the morphology and size of the array film can be effectively regulated by regulating the proportion of the precursor. The interlaced nanosheet array structure in this invention can make the electrolyte fully contact with the active material, increase the permeability of the electrolyte, and reduce the interface resistance; and the nanoarray grows directly on the titanium sheet current collector, shortening the ion transmission path and facilitating the transmission of electrons (CN201911049478.2). Han Yong et al. proposed a preparation process for a single / multiple element doped sodium titanate nanorod array coating, using a hydrothermal (HT) method to prepare different sodium titanate nanorod array coatings on the surface of pure titanium, and the above coatings were hydrothermally treated again to achieve single / multiple element (Mg, Ca, Sr or Zn) doping of nanorod-shaped sodium titanate in the coating (CN201811456718.6). Weijia Meng et al. proposed the design and preparation of hollow NTO microspheres (H-NTO) with oxygen defects, which are made of two-dimensional ultrathin nanosheets with a unique chemically bonded NTO / C (N) interface. The preparation is to first synthesize TiO2 microspheres by hydrothermal method, then synthesize NTO microspheres by hydrothermal method, and finally calcine the prepared NTO sample at 450℃ for 2 hours in Ar / H2 (95% / 5%) atmosphere. H-NTO as a negative electrode material for SIBs shows high specific capacity and excellent rate performance.
[0004] Wang Chao et al. proposed a potassium-doped sodium titanate electrode material and its preparation method and application. The potassium-doped sodium titanate electrode material has a rod-like layered structure and is synthesized by a simple solid-phase method. The precursors sodium carbonate, potassium carbonate and anatase phase titanium dioxide are ball-milled in proportion and then sintered in air by microwave. The addition of potassium increases the exposure of the (100) crystal plane of sodium titanate and reduces the exposure of the (003) crystal plane. This invention uses potassium-doped sodium titanate as a negative electrode material in sodium ion batteries. Due to the addition of potassium, the sodium ion diffusion channels become more numerous and shorter, which is beneficial to the storage of sodium ions, thereby improving the specific capacity and rate performance of the sodium titanate material (application number: CN202211220673.9). SDemirel et al. used Na2CO3, TiO2 and V2O5 powders to prepare Na2 Ti 6-x V x O 13 (where x = 0, 0.025, 0.05, 0.1) samples were prepared by heating the mixed powder at 800 °C for 16 h in air to remove carbonates in the structure. Then, a second heat treatment was performed at 1100 °C in air for 24 h to obtain the pure final powder. The electrochemical performance of the x = 0.05 substitution was higher than that of the undoped sample.
[0005] It can be seen that the existing sodium titanate doping technology is mainly focused on sodium titanate doping through the hydrothermal method. The titanium sources used are mostly expensive products such as tetrabutyl titanate and titanium metal. Although there are some innovations in the process and improvements in performance, there are also some potential disadvantages such as high cost, low repeatability, low yield, and difficulty in large-scale production. In addition, the process is complicated and will be accompanied by more energy consumption and labor costs. Even if the solid-phase doping method is currently used, although the process is simple and easy to scale up production, the titanium source is anatase titanium dioxide, which is relatively expensive, resulting in high cost of sodium titanate, and solid-phase doping is prone to uneven doping. Summary of the invention
[0006] In order to solve the above problems existing in the existing sodium titanate negative electrode material doping technology, the present invention provides a method for preparing a metal-doped sodium titanate negative electrode material.
[0007] The present invention provides a method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0008] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and metal A sulfate in water as a hydrolysis solution, wherein the molar ratio of A:Ti is 0.01-0.5:1;
[0009] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 80℃-110℃;
[0010] S3, hydrolysis: under stirring, the hydrolysis solution is added to the reactor at a uniform speed, and the temperature of the system in the reactor is kept constant. The hydrolysis reaction ends when the feeding is completed;
[0011] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying to obtain metal-doped metatitanic acid (HTO-A);
[0012] S5. Preparation of sodium titanate: uniformly mixing a sodium source and metal-doped metatitanic acid in a sodium to titanium molar ratio of 2:3, calcining under an argon atmosphere, and then naturally cooling to obtain metal-doped sodium titanate (NTO-A).
[0013] Furthermore, in step S1, A is one or a combination of K, Au, Cu, Zr, Mg, Nb, Ca, V, Sr, Mo, and Al.
[0014] Furthermore, the concentration of the hydrolysis solution in step S1 is 170-240 g / L.
[0015] Furthermore, in step S3, the stirring speed is 1000-1400 rpm.
[0016] Furthermore, the feed rate of the hydrolysis solution in step S3 is 1.0-5 mL / min.
[0017] Furthermore, during the feeding process in step S3, the system temperature is kept constant at 80°C-110°C.
[0018] Furthermore, the feeding time of the titanyl sulfate solution in step S3 is 1-12 hours.
[0019] Furthermore, in step S4, the drying temperature is 120° C. and the drying time is 10 hours.
[0020] Furthermore, in step S5, the sodium source is one or more of sodium acetate, sodium carbonate, sodium hydroxide, sodium oxalate, sodium oxide, and sodium peroxide.
[0021] Furthermore, the calcination in step S5 is as follows: heating to 800-950° C. at a heating rate of 5° C. / min, and keeping the temperature for 5-15 hours.
[0022] The present invention uses a sulfate solution of metal ions and a titanyl sulfate solution for hydrolysis to obtain metatitanic acid (HTO) uniformly doped with trace metal elements, and then the metatitanic acid and a sodium source are directly calcined to synthesize heterogeneous ion-regulated sodium titanate. Its beneficial technical effects are as follows:
[0023] 1. The present invention directly uses a sulfate solution of metal ions and a titanyl sulfate solution for hydrolysis. The metal ions affect the hydrolysis kinetics and change the particle size distribution and morphology characteristics of the product.
[0024] 2. The present invention directly dopes during the hydrolysis process, which can reduce the additional doping steps and the step of converting titanic acid into titanium dioxide, thereby reducing production costs and energy consumption, simplifying the operation process, and facilitating repeated experiments and scale-up.
[0025] 3. The present invention can make the metal ions more evenly distributed in the lattice of metatitanic acid, and then evenly distributed in the lattice of sodium titanate, thereby improving the quality of the sodium titanate product and being beneficial to improving its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM spectrum of the hydrolysis product HTO-Al in Example 1 of the present invention;
[0027] Figure 2 is the XRD spectrum of the hydrolysis product HTO-Al in Example 1 of the present invention;
[0028] Figure 3 This is the SEM spectrum of NTO-Al prepared in Example 1 of the present invention;
[0029] Figure 4 XRD spectrum of NTO-Al prepared in Example 1 of the present invention;
[0030] Figure 5 The mapping spectrum of NTO-Al prepared in Example 1 of the present invention;
[0031] Figure 6 The rate performance diagram of the NTO-Al negative electrode prepared in Example 1 of the present invention;
[0032] Figure 7 This is a performance diagram of the NTO-Al negative electrode prepared in Example 1 of the present invention after 200 cycles at 200 mA / g. DETAILED DESCRIPTION
[0033] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0034] Example 1
[0035] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0036] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and aluminum sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 240 g / L, and the molar ratio of Al:Ti is 0.12:1;
[0037] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 80°C;
[0038] S3, hydrolysis: under stirring at 1200 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 1.2 mL / min, and the temperature of the system in the reactor was kept constant at 80°C. The feeding time was 8 hours, and the hydrolysis reaction ended when the feeding was completed;
[0039] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain aluminum metal-doped metatitanic acid (HTOAl);
[0040] S5. Preparation of sodium titanate: Sodium hydroxide and aluminum-doped metatitanic acid (HTOAl) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 900° C. at a heating rate of 5° C. / min, kept at this temperature for 10 h, and then naturally cooled to obtain aluminum-doped sodium titanate (NTOAl).
[0041] Through detection, the aluminum metal doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the aluminum metal doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 153mAh / g at 100mA / g, a specific capacity of 114mAh / g at 2000mA / g, and a capacity retention rate of 74.5%; after 200 cycles at 200mA / g, the specific capacity is still 123mAh / g, and the capacity retention rate is 90%.
[0042] Example 2
[0043] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0044] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and molybdenum sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 170 g / L, and the molar ratio of Mo:Ti is 0.35:1.
[0045] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 110°C;
[0046] S3, hydrolysis: under stirring at 1000 rpm, the hydrolysis solution was uniformly added into the reactor at a feeding rate of 1.0 mL / min, and the temperature of the system in the reactor was kept constant at 110° C. The feeding time was 12 h, and the hydrolysis reaction ended when the feeding was completed;
[0047] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain molybdenum metal-doped metatitanic acid (HTOMo);
[0048] S5. Preparation of sodium titanate: Sodium acetate and molybdenum metal-doped metatitanic acid (HTOMo) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 800° C. at a heating rate of 5° C. / min, kept at this temperature for 15 h, and then naturally cooled to obtain molybdenum metal-doped sodium titanate (NTOMo).
[0049] Through detection, the molybdenum metal-doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the molybdenum metal-doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 204mAh / g at 100mA / g, a specific capacity of 120mAh / g at 2000mA / g, and a capacity retention rate of 58.8%; after 200 cycles at 200mA / g, the specific capacity is still 145mAh / g, and the capacity retention rate is 76%.
[0050] Example 3
[0051] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0052] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and gold sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 200 g / L, and the molar ratio of Au:Ti is 0.01:1.
[0053] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 90°C;
[0054] S3, hydrolysis: under stirring at 1100 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 1.3 mL / min, and the temperature of the system in the reactor was kept constant at 90° C. The feeding time was 6 h, and the hydrolysis reaction ended when the feeding was completed;
[0055] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain gold-doped metatitanic acid (HTOAu);
[0056] S5. Preparation of sodium titanate: Sodium carbonate and metal-doped metatitanic acid (HTOAu) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 850°C at a heating rate of 5°C / min, kept at this temperature for 8h, and then naturally cooled to obtain gold-doped sodium titanate (NTOAu).
[0057] Through detection, the gold-doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the gold-doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 234 mAh / g at 100 mA / g, a specific capacity of 137 mAh / g at 2000 mA / g, and a capacity retention rate of 58.5%; after 200 cycles at 200 mA / g, the specific capacity is still 160 mAh / g, and the capacity retention rate is 80%.
[0058] Example 4
[0059] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0060] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and potassium sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 210 g / L, and the molar ratio of K:Ti is 0.5:1.
[0061] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 100°C;
[0062] S3, hydrolysis: under stirring at 1400 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 1.4 mL / min, and the temperature of the system in the reactor was kept constant at 100° C. The feeding time was 3 h, and the hydrolysis reaction ended when the feeding was completed;
[0063] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain potassium metal-doped metatitanic acid (HTOK);
[0064] S5. Preparation of sodium titanate: Sodium oxalate and potassium metal-doped metatitanic acid (HTOK) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 950° C. at a heating rate of 5° C. / min, kept at this temperature for 5 h, and then naturally cooled to obtain potassium metal-doped sodium titanate (NTOK).
[0065] Through detection, the potassium metal-doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the potassium metal-doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 140 mAh / g at 100 mA / g, a specific capacity of 89 mAh / g at 2000 mA / g, and a capacity retention rate of 63.6%; after 200 cycles at 200 mA / g, the specific capacity is still 111 mAh / g, and the capacity retention rate is 72%.
[0066] Example 5
[0067] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0068] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and copper sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 220 g / L, and the molar ratio of Cu:Ti is 0.44:1.
[0069] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 85°C;
[0070] S3, hydrolysis: under stirring at 1050 rpm, the hydrolysis solution was uniformly added into the reactor at a feeding rate of 1.5 mL / min, and the temperature of the system in the reactor was kept constant at 85°C. The feeding time was 1 h, and the hydrolysis reaction ended when the feeding was completed;
[0071] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain copper metal-doped metatitanic acid (HTOCu);
[0072] S5. Preparation of sodium titanate: Sodium oxide and copper-doped metatitanic acid (HTOCu) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 880°C at a heating rate of 5°C / min, kept at this temperature for 7 hours, and then naturally cooled to obtain copper-doped sodium titanate (NTOCu).
[0073] Through detection, the copper metal doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the copper metal doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 185 mAh / g at 100 mA / g, a specific capacity of 127 mAh / g at 2000 mA / g, and a capacity retention rate of 68.6%; after 200 cycles at 200 mA / g, the specific capacity is still 139 mAh / g, and the capacity retention rate is 80%.
[0074] Example 6
[0075] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0076] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and zirconium sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 190 g / L, and the molar ratio of Zr:Ti is 0.08:1.
[0077] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 95°C;
[0078] S3, hydrolysis: under stirring at 1050 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 1.1 mL / min, and the temperature of the system in the reactor was kept constant at 95°C. The feeding time was 10 h, and the hydrolysis reaction ended when the feeding was completed;
[0079] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain zirconium metal-doped metatitanic acid (HTOZr);
[0080] S5. Preparation of sodium titanate: sodium peroxide and zirconium metal-doped metatitanic acid (HTOZr) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 850°C at a heating rate of 5°C / min, kept at this temperature for 13 hours, and then naturally cooled to obtain zirconium metal-doped sodium titanate (NTOZr).
[0081] Through detection, the zirconium metal doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the zirconium metal doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 174 mAh / g at 100 mA / g, a specific capacity of 131 mAh / g at 2000 mA / g, and a capacity retention rate of 75.3%; after 200 cycles at 200 mA / g, the specific capacity is still 126 mAh / g, and the capacity retention rate is 75%.
[0082] Example 7
[0083] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0084] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and magnesium sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 230 g / L, and the molar ratio of Mg:Ti is 0.27:1.
[0085] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 105°C;
[0086] S3, hydrolysis: under stirring at 1100 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 1.2 mL / min, and the temperature of the system in the reactor was kept constant at 105°C. The feeding time was 7 hours, and the hydrolysis reaction ended when the feeding was completed;
[0087] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain magnesium metal-doped metatitanic acid (HTOMg);
[0088] S5. Preparation of sodium titanate: Sodium hydroxide and magnesium metal-doped metatitanic acid (HTOMg) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 800°C at a heating rate of 5°C / min, kept at this temperature for 15 hours, and then naturally cooled to obtain magnesium metal-doped sodium titanate (NTOMg).
[0089] Through detection, the magnesium metal-doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the magnesium metal-doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 193mAh / g at 100mA / g, a specific capacity of 129mAh / g at 2000mA / g, and a capacity retention rate of 66.8%; after 200 cycles at 200mA / g, the specific capacity is still 133mAh / g, and the capacity retention rate is 80%.
[0090] Example 8
[0091] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0092] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and niobium sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 185 g / L, and the molar ratio of Nb:Ti is 0.4:1.
[0093] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 80°C;
[0094] S3, hydrolysis: under stirring at 1200 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 1.3 mL / min, and the temperature of the system in the reactor was kept constant at 80° C. The feeding time was 6 h, and the hydrolysis reaction ended when the feeding was completed;
[0095] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain niobium metal-doped metatitanic acid (HTONb);
[0096] S5. Preparation of sodium titanate: Sodium acetate and niobium metal-doped metatitanic acid (HTONb) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 900° C. at a heating rate of 5° C. / min, kept at this temperature for 6 h, and then naturally cooled to obtain niobium metal-doped sodium titanate (NTONb).
[0097] Through detection, the niobium metal-doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the niobium metal-doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 225 mAh / g at 100 mA / g, a specific capacity of 141 mAh / g at 2000 mA / g, and a capacity retention rate of 62.7%; after 200 cycles at 200 mA / g, the specific capacity is still 147 mAh / g, and the capacity retention rate is 77%.
[0098] Example 9
[0099] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0100] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and calcium sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 180 g / L, and the molar ratio of Ca:Ti is 0.16:1.
[0101] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 90°C;
[0102] S3, hydrolysis: under stirring at 1300 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 1.4 mL / min, and the temperature of the system in the reactor was kept constant at 90° C. The feeding time was 5 h, and the hydrolysis reaction ended when the feeding was completed;
[0103] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain calcium metal-doped metatitanic acid (HTOCa);
[0104] S5. Preparation of sodium titanate: Sodium oxalate and calcium metal-doped metatitanic acid (HTOCa) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 950°C at a heating rate of 5°C / min, kept at this temperature for 5 hours, and then naturally cooled to obtain calcium metal-doped sodium titanate (NTOCa).
[0105] Through detection, the calcium metal-doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the calcium metal-doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 135 mAh / g at 100 mA / g, a specific capacity of 92 mAh / g at 2000 mA / g, and a capacity retention rate of 68.1%; after 200 cycles at 200 mA / g, the specific capacity is still 115 mAh / g, and the capacity retention rate is 70%.
[0106] Example 10
[0107] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0108] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and vanadium sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 235 g / L, and the molar ratio of V:Ti is 0.22:1.
[0109] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 110°C;
[0110] S3, hydrolysis: under stirring at 1400 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 1.2 mL / min, and the temperature of the system in the reactor was kept constant at 110° C. The feeding time was 9 h, and the hydrolysis reaction ended when the feeding was completed;
[0111] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain vanadium metal-doped metatitanic acid (HTOV);
[0112] S5. Preparation of sodium titanate: Sodium carbonate and vanadium-doped metatitanic acid (HTOV) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 850° C. at a heating rate of 5° C. / min, kept at this temperature for 12 h, and then naturally cooled to obtain vanadium-doped sodium titanate (NTOV).
[0113] Through detection, the vanadium metal-doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the vanadium metal-doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 163mAh / g at 100mA / g, a specific capacity of 99mAh / g at 2000mA / g, and a capacity retention rate of 60.7%; after 200 cycles at 200mA / g, the specific capacity is still 125mAh / g, and the capacity retention rate is 75%.
[0114] Embodiment 11
[0115] A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps:
[0116] S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and strontium sulfate in water as a hydrolysis solution, wherein the concentration of the hydrolysis solution is 205 g / L, and the molar ratio of Sr:Ti is 0.05:1.
[0117] S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 80°C;
[0118] S3, hydrolysis: under stirring at 1300 rpm, the hydrolysis solution was uniformly added to the reactor at a feeding rate of 13 mL / min, and the temperature of the system in the reactor was kept constant at 80° C. The feeding time was 8 h, and the hydrolysis reaction ended when the feeding was completed;
[0119] S4, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying at 120° C. for 10 h to obtain strontium metal-doped metatitanic acid (HTOSr);
[0120] S5. Preparation of sodium titanate: Sodium hydroxide and strontium metal-doped metatitanic acid (HTOSr) are uniformly mixed in a sodium to titanium molar ratio of 2:3, calcined in an argon atmosphere, heated to 800° C. at a heating rate of 5° C. / min, kept warm for 13 h, and then naturally cooled to obtain strontium metal-doped sodium titanate (NTOSr).
[0121] Through detection, the strontium metal-doped metatitanic acid prepared in step S4 is a micron sphere with uniform particle size, smooth and dense surface, and a particle size of 5-10 microns; the strontium metal-doped sodium titanate negative electrode material prepared in step S5 has a specific capacity of 182mAh / g at 100mA / g, a specific capacity of 118mAh / g at 2000mA / g, and a capacity retention rate of 64.8%; after 200 cycles at 200mA / g, the specific capacity is still 148mAh / g, and the capacity retention rate is 84%.
[0122] Further analysis with attached figures:
[0123] Figure 1 This is the SEM spectrum of the hydrolysis product HTO-Al in Example 1 of the present invention; Figure 2 This is the XRD spectrum of the hydrolysis product HTO-Al in Example 1 of the present invention. It can be seen that HTO-Al is a micron sphere with uniform particle size, smooth and dense surface, and the overall particle size is about 5-10 microns, corresponding to the peak of anatase titanium dioxide.
[0124] Figure 3 This is the SEM spectrum of NTO-Al prepared in Example 1 of the present invention; Figure 4 XRD spectrum of NTO-Al prepared in Example 1 of the present invention; Figure 5 The mapping spectrum of NTO-Al prepared in Example 1 of the present invention. It can be seen that NTO-Al is a relatively solid micron sphere with nanorods grown on the surface. The overall particle size is about 5-10 microns and the sphericity is intact; XRD mainly corresponds to Na2Ti3O7 and Na2Ti6O 13 The mapping diagram shows that Al is uniformly doped.
[0125] Figure 6 From the rate performance diagram of the NTO-Al negative electrode prepared in Example 1 of the present invention, it can be seen that the specific capacity of NTO-Al is 153 mAh / g at 100 mA / g, the specific capacity is 114 mAh / g at 2000 mA / g, and the capacity retention rate is 74.5%.
[0126] Figure 7 This is a performance diagram of the NTO-Al negative electrode prepared in Example 1 of the present invention after 200 cycles at 200 mA / g. It can be seen that the specific capacity of the NTO-Al negative electrode is still 123 mAh / g after 200 cycles at 200 mA / g, and the capacity retention rate is as high as 90%.
[0127] In summary, the present invention uses a sulfate solution and a titanyl sulfate solution mixed with metal ions for hydrolysis to obtain metatitanic acid (HTO) uniformly doped with trace metal elements, and then directly calcining metatitanic acid and a sodium source to synthesize heterogeneous ion-regulated sodium titanate. The present invention simplifies the process, and doping directly during the hydrolysis process can reduce additional doping steps, and reduces the steps of converting metatitanic acid into titanium dioxide, reduces production costs and energy consumption, simplifies the operating process, and facilitates repeated experiments and scale-up. In addition, doping during the hydrolysis process can make the metal ions more evenly distributed in the lattice of metatitanic acid, thereby improving the quality of the sodium titanate product. In addition, through the action of metal ions, the metatitanic acid generated by hydrolysis is a micron sphere with uniform particle size and smooth and dense surface. The sodium titanate prepared after calcination can better maintain the spherical shape, thereby improving its performance in electrochemical energy storage devices.
[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal-doped sodium titanate negative electrode material, the preparation method comprising the following steps: S1. Preparation of hydrolysis solution: dissolving titanyl sulfate and metal A sulfate in water as a hydrolysis solution, wherein the molar ratio of A:Ti is 0.01-0.5:1; S2. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 80℃-110℃; S3, hydrolysis: under stirring, the hydrolysis solution is added to the reactor at a uniform speed, and the temperature of the system in the reactor is kept constant. The hydrolysis reaction ends when the feeding is completed; S4, preparing titanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying to obtain metal-doped titanic acid; S5. Preparation of sodium titanate: uniformly mixing a sodium source and metal-doped metatitanic acid in a sodium to titanium molar ratio of 2:3, calcining the mixture under an argon atmosphere, and then cooling the mixture naturally to obtain metal-doped sodium titanate.
2. The method for preparing the metal-doped sodium titanate negative electrode material according to claim 1, characterized in that: In step S1, A is one or a combination of K, Au, Cu, Zr, Mg, Nb, Ca, V, Sr, Mo, and Al.
3. The method for preparing the metal-doped sodium titanate negative electrode material according to claim 1, characterized in that: The concentration of the hydrolysis solution in step S1 is 170-240 g / L.
4. The method for preparing the metal-doped sodium titanate negative electrode material according to claim 1, characterized in that: The stirring speed in step S3 is 1000-1400 rpm.
5. The method for preparing the metal-doped sodium titanate negative electrode material according to claim 1, characterized in that: The feed rate of the hydrolysis solution in step S3 is 1.0-5 mL / min.
6. The method for preparing the metal-doped sodium titanate negative electrode material according to claim 1, characterized in that: During the feeding process in step S3, the system temperature is kept constant at 80°C-110°C.
7. The method for preparing the metal-doped sodium titanate negative electrode material according to claim 1, characterized in that: The feeding time of the titanyl sulfate solution in step S3 is 1-12 hours.
8. The method for preparing the metal-doped sodium titanate negative electrode material according to claim 1, characterized in that: In step S4, the drying temperature is 120° C. and the drying time is 10 hours.
9. The method for preparing the metal-doped sodium titanate negative electrode material according to claim 1, characterized in that: In step S5, the sodium source is one or more of sodium acetate, sodium carbonate, sodium hydroxide, sodium oxalate, sodium oxide, and sodium peroxide.
10. The method for preparing a metal-doped sodium titanate negative electrode material according to any one of claims 1 to 9, characterized in that: The calcination in step S5 is as follows: heating to 800-950° C. at a heating rate of 5° C. / min and keeping the temperature for 5-15 hours.
Citation Information
Patent Citations
Preparation process of single / multiple-element doped sodium titanate nanorod array coatings
CN109568655A
Iron in-situ doped sodium titanate electrode material and preparation method thereof
CN110931264A
Potassium-doped sodium titanate electrode material and preparation method and application thereof
CN115472800A
Nickel-doped sodium titanate / graphene composite material and preparation method thereof
CN118016838A
A sulfate process
CN101553585A
Cited By
Doped sodium trititanate composite material as well as preparation method and application thereof
CN120749161A
Double-element synergistically-doped sodium titanate negative electrode material and preparation method and application thereof
CN122202294A